2019
DOI: 10.1186/s12887-019-1761-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of QuickVue® Dipstick Strep A test and its effect on antibiotic prescribing in children in the United Arab Emirates

Abstract: BackgroundUnnecessary antibiotic prescription to patients with upper respiratory tract infections (URTIs) has led to the increase in antibiotics resistant bacteria rates. In this study, we evaluated the diagnostic accuracy of QuickVue® Dipstick Strep A test (QV-SAT) in children presenting with acute pharyngotonsillitis and its effect on antibiotic prescribing.MethodsA single-gated diagnostic accuracy study of children with fever, runny nose, and tonsillitis presenting to a paediatric clinic between March 2016 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…This could be attributed to the higher sensitivity of the FIA-RADT compared to the standard culture method as discussed below. The sensitivity and specificity of the FIA-RADT in our study were very high; however, the percentages were lower than those reported in a recent study from the United Arab Emirates (UAE) [21]. This can be explained by the fact that 70 % of the population in the UAE study comprised children under 5 years of age, who are known to have low incidence of group A streptococcal pharyngitis.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…This could be attributed to the higher sensitivity of the FIA-RADT compared to the standard culture method as discussed below. The sensitivity and specificity of the FIA-RADT in our study were very high; however, the percentages were lower than those reported in a recent study from the United Arab Emirates (UAE) [21]. This can be explained by the fact that 70 % of the population in the UAE study comprised children under 5 years of age, who are known to have low incidence of group A streptococcal pharyngitis.…”
Section: Discussioncontrasting
confidence: 88%
“…A study from Egypt found that the antibiotic prescription rate in three centres for cases of pharyngitis was ~86 % [31]. Multiples studies indicated that RADT decreases unnecessary antibiotic prescription for non-GAS pharyngitis [21, 32]. Our study showed that the estimated effect of FIA-RADT implementation in clinical practice could reduce the frequency of unnecessary antibiotic prescriptions by approximately 28 %.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation